The longitudinal connection between depressive symptoms and inflammation: Mediation by sleep quality. - Sunmi Song; Natasha N DeMeo; David M Almeida; Marzieh Majd; Christopher G Engeland; Jennifer E Graham-Engeland (PLoS ONE, 2022)
Although there is a strong association between depressive symptoms and markers of inflammation, it remains unclear whether depressive symptoms at one point in life may predict inflammation later in life. Moreover, despite extant literature linking sleep with both depressive symptoms and inflammation, there is little research investigating poor sleep as a mechanism linking depressive symptoms with later inflammation. The links between depression and physical health can also vary by gender. In longitudinal analyses with data from the Midlife in the United States (MIDUS) study, we examined whether depressive symptoms were associated with inflammatory markers 11 years later and whether these associations were mediated by sleep disturbances or moderated by gender. Participants reported depressive symptoms and demographic information at baseline. At 11-year follow-up, the same participants (n = 968) reported depressive symptoms, sleep quality and duration using validated scale items, and provided a blood sample from which inflammatory markers interleukin-6 (IL-6) and C-reactive protein (CRP) were quantified. Actigraphy assessment of sleep was obtained in a subsample (n = 276). After adjusting for concurrent depressive symptoms and other relevant covariates, baseline depressive symptoms were associated with CRP 11 years later in the full sample, and with IL-6 among women. Subjective sleep quality mediated the association between depressive symptoms and CRP. Results suggest that depressive symptoms may be longitudinally associated with inflammation; however, directionality issues cannot be determined from the present work, particularly as inflammation markers (which might have been associated with baseline depressive symptoms) were not available at baseline. Findings further suggest that longitudinal associations between depressive symptoms and inflammation may potentially be explained by sleep and may reflect gender specific patterns.